A Daoist Reflection on Sea-Like Leadership and Enlightened Thinking. (28th December 2016) - Xing, Yijun
Abstract : As he gazed on the sea, Confucius sighed: 'The passage of time is like the flow of water, which goes on day and night'. In later generations, the image of 'water' was found everywhere in Chinese literature, and most works used the metaphor first expressed by Confucius (Xing & Liu, 2015 ). However, Lao Zi's understanding differed from Confucius's, as he was more concerned with the virtues of water than its image. He believed that 'the highest virtue is like that of water. Water benefits everything in the world without contending'.